Lessons for promotion of new agricultural technology: a case of Vijay wheat variety in Nepal - Timsina, Krishna Prasad; Ghimire, Y.N.; Gauchan, D.; Subedi, S.; Adhikari, S.P. (Springer, 2018)
It seems that the current production of Vijay’s breeder seed is more than enough to cultivate in total wheat area in Terai of Nepal if proper seed cycle is maintained. But this is not in reality. NARC should decentralized foundation seed to private actors such as private seed companies, national seed companies and community-based organizations to maximize the resource use efficiency in the seed cycle through introducing effective monitoring and technical backstopping mechanism from public sector. Therefore, the close coordination and commitment of the public and private seed companies, community seed groups, cooperatives and public extension agencies to multiply seeds in subsequent cycles is required. Moreover, awareness program about superiority of Vijay with other improved wheat varieties should be emphasized for the rapid commercialization of the Vijay seed which would be an instrumental to mitigate the potential epidemics of newly emerging pathotype of stem rust (Ug99) in the future.